THE EFFECTIVENESS OF USING MEGURO LANGUAGE CENTER FLASH MEDIA IN JAPANESE INTRANSITIVE AND TRANSITIVE VERB PAIRS LEARNING (True Experimental Research for Second Grade Students of UPI’s Japanese Language Education Departement) - Haryani, Nia; Aneros, Noviyanti; Herniwati, Herniwati (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2016)
Abstract. Japanese intransitive and transitive verb pairs (jidoushi and tadoushi pairs) are still one of difficult things for Japanese language learners. Results of questionnaire mentioned that difficulties experienced by a student are distinguish between intransitive and transitive verb pairs, and use of intransitive and transitive verb pairs in Japanese sentence. Therefore, we have to use an effective media on intransitive and transitive verb pairs learning, on purpose to decrease that difficulties. The purpose of this research are (1) to know any significant difference in learners ability in intransitive and transitive verb pairs vocabulary and know how to using intransitive and transitive verb pairs in Japanese sentence before and after using Meguro language center (MLC) flash media; (2) to determine the effectiveness of using MLC flash media in intransitive and transitive verb pairs learning; (3) to determine learners response of using MLC flash media in intransitive and transitive verb pairs learning. This research use the true experiment design, and also use the test and questionnaire to get some data’s. The research object is second grade students of UPI’s Japanese language education departement of the academic year 2015/2016, and the samples are students at 4B as experimental group and students 4C as control group. From the result of data analysis obtained that value is 2,46 and value is 2,07 at 5% significance level. Because is greater than so Hk accepted. Then from normalized gain mean, experimental group gained 0,67 is approving of MLC flash media is more effective as compared with text media. In addition, analysis of questionnaire showed that student has given a positive response to application of MLC flash media. Keywords : Japanese intransitive and transitive verb pairs, jidoushi and tadoushi pairs, learning media, flash, Meguro language center  Abstrak. Bagi pembelajar bahasa Jepang, jidoushi dan tadoushi berpasangan masih menjadi hal yang sulit. Hasil angket menyebutkan bahwa kesulitan yang dialami pembelajar adalah kesulitan dalam membedakan jidoushi dan tadoushi berpasangan dan kesulitan dalam penggunaan kedua verba tersebut dalam suatu kalimat. Diperlukan suatu media yang efektif dalam pembelajaran jidoushi dan tadoushi berpasangan agar kesulitan tersebut dapat dikurangi. Penelitian ini bertujuan (1) untuk mengetahui adakah perbedaan yang signifikan mengenai kemampuan pembelajar dalam menguasai kosakata dan memahami penggunaan jidoushi dan tadoushi berpasangan sebelum dan sesudah proses pembelajaran menggunakan media flash Meguro language center (MLC); (2) untuk mengetahui tingkat efektivitas penggunaan media flash MLC terhadap kemampuan pembelajar dalam menguasai kosakata dan memahami penggunaan jidoushi dan tadoushi berpasangan; (3) untuk mengetahui tanggapan pembelajar terhadap penggunaan media flash MLC dalam pembelajaran jidoushi dan tadoushi berpasangan. Penelitian ini menggunakan metode penelitian eksperimen murni. Adapun instrumen yang digunakan, yaitu tes dan angket. Sampel yang digunakan yaitu mahasiswa tingkat II Departemen Pendidikan Bahasa Jepang UPI tahun ajaran 2015/2016 kelas 4B sebagai kelompok eksperimen dan kelas 4C sebagai kelompok kontrol yang masing-masing kelas diambil sebanyak 12 orang. Dari hasil analisis data setelah melakukan penelitian, diperoleh nilai sebesar 2,46 dan nilai 2,07 pada taraf signifikansi 5%. Karena hasil lebih besar dari  maka Hk diterima. Kemudian dari nilai rata-rata normalized gain kelas eksperimen yaitu sebesar 0,67 membuktikan bahwa menggunakan media flash MLC lebih efektif dibandingkan dengan media teks. Kemudian berdasarkan pengolahan angket menunjukan bahwa pembelajar memberikan respon yang positif terhadap penggunaan media flash MLC. Kata kunci : Jidoushi dan tadoushi berpasangan, media pembelajaran, flash,  Meguro language center